The relationship of certain variables to academic achievement among UP High School freshmen - Bartolome, Claribel Diaz 1946- (s.n.], 1972)
The study habits and attitudes, and personality factors contributing to the adjustment of the UP High School freshmen enrolled during the school year 1971-1972 were identified, and these variables were related to academic achievement.